The origins of the concepts of Shi'ism and Sunnism - Spahic, Omer (Amana Publications, 2016)
This book examines the origins of the concepts of Shi’ism and Sunnism (ahl al-sunnah wa al-jama’ah). It deals with the factors, personnel and circumstances that were most decisive in the creation and evolution of the two poles. The nature and scope of some early institutionalized Sunni-Shi’ah conflicts are also explored. The book is divided into three chapters. In the first chapter, the origins of Shi’ism between politics, creed and fanaticism are discussed. Therein the main thrusts of Shi’ism from the perspectives of both Shi’is and Sunnis are critically explored -- as is the evolution of Shi’ism from sheer political activism to a comprehensive ideology. Analyzing the conceptual and socio-political relationships between the notion of shi’atu ‘Ali (‘Ali’s party) and all the manifestations of the concept’s unorthodox derivatives, is undertaken as well. Finally, the question of whether there could be such thing as “Sunni Shi’ism”, and what exactly that would entail, is asked and meticulously answered. In the second chapter, the subject of the origins and evolution of the concept of ahl al-sunnah wa al-jama’ah is thoroughly examined. The religious, socio-political and historical contexts of the concept’s development are investigated. The chapter firstly delves into the issues of Islam as a religion of human dignity and honor, and the importance of unity and concord in Islam, as both preconditions for, and ultimate objectives of, the ahl al-sunnah wa al-jama’ah factor. Central to the chapter is the theme of the evolution of the concept of ahl al-sunnah wa al-jama’ah from an embryonic concept of ahl al-sunnah to a comprehensive and full-fledged concept of ahl al-sunnah wa al-jama’ah. The conditions under which the ahl al-sunnah wa al-jama’ah idiom became synonymous with mainstream orthodox Islam, are discussed too. Finally, in the third chapter, the role of the Shi’ah Fatimids in intensifying and cementing Sunni-Shi’ah conflicts, specifically at the level of institutions, and the immediate repercussions of such role, are looked into. To what extent the realms of art and architecture have been employed for the purpose are also at the end investigated. Notwithstanding a few relatively sensitive aspects of the book, it has been researched and written in good faith. Nothing but an honest intellectual discourse was thereby intended, aiming to promote and advance the prospect of Sunni-Shi’ah dialogue. Lastly, I welcome any constructive and academic suggestions or comments concerning the book’s content, such as my methodology, arguments, inferences, and the nature of the collected data and my understanding and interpretation of them.